2021
DOI: 10.1016/j.pmedr.2021.101400
|View full text |Cite
|
Sign up to set email alerts
|

Link between redemption of a medical food pantry voucher and reduced hospital readmissions

Abstract: This study investigated the relationship between redeeming a voucher at hospital-based Medical Food Pantry (MFP) and hospital readmissions in Greenville, NC. Admitted patients at Vidant Medical Center identified as food insecure were given a voucher to the MFP. A retrospective chart review identified demographic information, type of insurance, voucher provision, and redemption dates, food bag type and number of subsequent hospital readmissions for all patients issued a voucher (n = 542) between June 21, 2018 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Building on our previous research, that demonstrated potential to reduce readmissions overall, this could save an estimated $13,464.87 to $15,238.63 per inpatient readmission. (20) The impact of medically tailored food on healthcare utilization was also comparable between our study and Berkowitz et al ( 2019). (21) In both studies individuals who experienced FIS but did not receive the medically tailored food interventions had higher readmissions (1.4 MFP vs. 1.6 MTM) which suggests provision of food may offer reduced healthcare utilization and therefore associated costs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Building on our previous research, that demonstrated potential to reduce readmissions overall, this could save an estimated $13,464.87 to $15,238.63 per inpatient readmission. (20) The impact of medically tailored food on healthcare utilization was also comparable between our study and Berkowitz et al ( 2019). (21) In both studies individuals who experienced FIS but did not receive the medically tailored food interventions had higher readmissions (1.4 MFP vs. 1.6 MTM) which suggests provision of food may offer reduced healthcare utilization and therefore associated costs.…”
Section: Discussionsupporting
confidence: 91%
“…(14) Previously we established that redemption of an MFP voucher by FIS patient to meet immediate nutrition needs was associated with reduced hospital readmissions. (20) This study compares the cost of implementing an MFP to the cost of hospital utilization associated with unmet social and nutritional needs in rural, southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…47 Some environmental factors have been linked to increased readmission risk in other disease models but not yet evaluated in dementia populations. [48][49][50] Beyond residential segregation, which may influence the types of health-related resources one has access to, discriminatory structural pathways are also present within the healthcare system. Hospital segregation has been documented for decades, and structurally shapes racial differences in access to specialized services, quality of providers, and medical practice patterns.…”
Section: Discussionmentioning
confidence: 99%
“…With further optimization of our screening workflow and the process by which food insecure patients are connected to resources, and follow-up to ensure that patients are using the resources provided, we hope our efforts will mitigate the high prevalence of food insecurity in Monroe County. 2 A reduction in food insecurity is expected to reduce healthcare costs [10][11][12] and improve overall patient health, including cardiometabolic risk 4 and glycemic control. 7 The insights gathered through our pilot have informed the implementation of a new hospital-wide EHR system for documenting SDoH.…”
Section: Discussionmentioning
confidence: 99%
“…7 Food insecurity has also been linked to higher use of acute-care services 9,10 and increased hospital readmissions. 11 During the COVID-19 pandemic, rates of food insecurity increased across the nation [12][13][14][15] in the setting of rising unemployment rates, reduced access to food and transportation, and safety concerns. The pandemic has also highlighted existing inequalities, with a disproportionate rise in food insecurity among racial minorities and households with children.…”
Section: Introductionmentioning
confidence: 99%